Nationwide and long-term molecular epidemiologic studies of mumps viruses that circulated in Japan between 1986 and 2017 - Kidokoro, Minoru; Shiino, Teiichiro; Yamaguchi, Tomohiro; Nariai, Eri; Kodama, Hiroe; Nakata, Keiko; Sano, Takako; Gotou, Keiko; Kisu, Tomoko; Maruyama, Tomomi; Kuba, Yumani; Sakata, Wakako; et al. (Frontiers in Microbiology, 2022)
In Japan, major mumps outbreaks still occur every 4–5 years because of low mumps vaccine coverage (30–40%) owing to the voluntary immunization program. Herein, to prepare for a regular immunization program, we aimed to reveal the nationwide and long-term molecular epidemiological trends of the mumps virus (MuV) in Japan. Additionally, we performed whole-genome sequencing (WGS) using next-generation sequencing (NGS) to assess results from conventional genotyping using MuV sequences of the small-hydrophobic (SH) gene. We analyzed 1,064 SH gene sequences from mumps clinical samples and MuV isolates collected from 25 prefectures from 1986 to 2017. The results showed that six genotypes, namely B, F, G, H, J, and L were identified, and the dominant genotypes changed every decade in Japan since the 1980s. Genotype G has been exclusively circulating since the early 2000s. Seven clades were identified for genotype G using SH sequence-based classification. To verify the results, we performed WGS on 28 representative isolates of genotype G using NGS and phylogenetically analyzed them. Five clades were identified with high bootstrap values and designated as Japanese clade (JPC)-1, -2, -3, -4, -5. JPC-1 and -3 accounted for over 80% of the total genotype G isolates (68.3 % and 13.8 %, respectively). Furthermore, two novel clades, JPC-2 and -5, were identified. This is the first report describing the nationwide and long-term molecular epidemiology of MuV in Japan. The results provide information about Japanese domestic genotypes, which is essential for evaluating the mumps elimination progress in Japan after the forthcoming introduction of the mumps vaccine into Japan’s regular immunization program. Furthermore, the study shows that WGS analysis using NGS is more accurate than results obtained from conventional SH sequence-based classification and is a powerful tool for accurate molecular epidemiology studies.